IBM z/OS V2R2 security - Winnard, Keith (IBM redbooks, 2015)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced to the security areas with IBM z/OS® V2R2. The following chapters are included: - Chapter 1, "RACF updates" on page 1: In this chapter, we describe the read-only auditor attribute, password security enhancements, RACDCERT (granular certificate administration), UNIX search authority, and RACF Remote sharing facility (RRSF). - Chapter 2, "LDAP updates" on page 13: In this chapter, we describe the activity log enhancements, compatibility level upgrade without LDAP outage, dynamic group performance enhancements, and replication of password policy attributes from a read-only replica. - Chapter 3, "PKI updates" on page 21: In this chapter, we describe the Network Authentication Service (KERBEROS) PKINIT, PKI nxm authorization, PKI OCSP enhancement, and RACDCERT (granular certificate administration) - Chapter 4, "z/OS UNIX search and file execution authority" on page 27: z/OS UNIX search authority, z/OS UNIX file execution, Examples for exploiting the new functions This book is one of a series of IBM Redbooks that take a modular approach to providing information about the updates that are included with z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful and we welcome your feedback.